Evaluation of analogues of furan-amidines as inhibitors of NQO2. Issue 8 (1st May 2018) - Alnabulsi, Soraya; Hussein, Buthaina; Santina, Elham; Alsalahat, Izzeddin; Kadirvel, Manikandan; Magwaza, Rachael N.; Bryce, Richard A.; Schwalbe, Carl H.; Baldwin, Alex G.; Russo, Ilaria; Stratford, Ian J.; Freeman, Sally
Graphical abstract: Abstract: Inhibitors of the enzyme NQO2 (NRH: quinone oxidoreductase 2) are of potential use in cancer chemotherapy and malaria. We have previously reported that non-symmetrical furan amidines are potent inhibitors of NQO2 and here novel analogues are evaluated. The furan ring has been changed to other heterocycles (imidazole, N -methylimidazole, oxazole, thiophene) and the amidine group has been replaced with imidate, reversed amidine, N -arylamide and amidoxime to probe NQO2 activity, improve solubility and decrease basicity of the lead furan amidine. All compounds were fully characterised spectroscopically and the structure of the unexpected product N -hydroxy-4-(5-methyl-4-phenylfuran-2-yl)benzamidine was established by X-ray crystallography. The analogues were evaluated for inhibition of NQO2, which showed lower activity than the lead furan amidine. The observed structure-activity relationship for the furan-amidine series with NQO2 was rationalized by preliminary molecular docking and binding mode analysis. In addition, the oxazole-amidine analogue inhibited the growth of Plasmodium falciparum with an IC50 value of 0.3 μM.